Ginkgo biloba L. extract and flunixin meglumine attenuate sepsis–associated liver injury, oxidative stress, inflammation and apoptosis in rats - Parlak Ak, Tuba; Gul, Burcu; Yaman, Mine; Seven, Ismail; Dagoglu, Gurdal; Gul, Huseyin Fatih (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Lipopolysaccharide (LPS), known as a stimulant of inflammation, causes acute liver injury by inducing the production of inflammatory mediators and oxidative stress. The purpose of this study is to determine whether of a nonsteroidal anti–inflammatory drug (NSAID) Flunixin meglumine (FM) and herbal an medicine Ginkgo biloba L. extract (GBE) show antioxidative, anti–inflammatory or antiapoptotic effects in liver tissue in LPS–induced hepatotoxicity. Animals were separated to 6 groups as control, sepsis (1 mg·kg-1, 7th day single dose, intraperitoneal (ip)), sepsis + FM (1 mg·kg-1, 7th day single dose, ip + 2.2 mg·kg-1 day, ip), sepsis + GBE (1 mg·kg-1, 7th day single dose, ip + 50 mg·kg-1 day, gavage), FM and GBE and the study continued for 7 days. Liver tissues taken from rats sacrificed were analyzed biochemically, histologically and immunohistochemically. Accordingly, LPS caused liver function markers alteration, inflammation, oxidative stress, and apoptosis, as well as histopathological changes in liver tissue. However, it was observed that LPS–induced changes were regulated by FM and GBE application. FM and GBE was demonstrated to have antioxidant, antiinflammatory and anti–apoptotic properties in LPS–induced hepatotoxicity.